Internal Creative Economy-Based MSME Development Strategy Obtaining Profit Margin in Tompotikka Village, Palopo City - Lutfi Uluelang, Muhammad; Sucianti, Riska; Fadillah, Andi Nur; Rizal, Rizal (Universitas Negeri Makassar, 2023)
Creative economy-based MSMEs in optimizing profit margins in Tompotikka Village, Palopo City, namely by using the first strategy, the price offered greatly influences income because the more affordable the price, the more people will be interested in buying products from an MSME. Second, the strategy that is most widely used is the fifth strategy, namely that products have various variants. The more types of products offered, the more choices and interest there will be in shopping at an MSME. Third, the most widely used strategy is the simplest strategy, namely promotion carried out on the internet media. It cannot be denied that nowadays the use of internet media has a big influence on income because there is a lot of internet use not only among teenagers but also among adults and adults. children. Fourth, the strategy that is widely used is strategy seven, namely the product is sold to the figure exclusively. This strategy allows the public to know the place and not need to look for where to buy products from MSMEs, just come to the figure, the community can immediately enjoy it. Fifth, the strategy that is widely used is the third strategy, namely the product model following current fashion trends. If a business continues to develop its business by looking at the latest trends, the greater the profits it will be in seeing the needs of society which are always changing at any time and with the times. Sixth, the strategy that is widely used is the sixth strategy, namely that the product is not easily damaged. The stronger the product from an MSME, the greater the consumer's desire to buy because they will think about how to use a product so that it can be used for a long time.